2015
DOI: 10.1007/s11682-015-9454-9
|View full text |Cite
|
Sign up to set email alerts
|

Problematic internet use is associated with structural alterations in the brain reward system in females

Abstract: Neuroimaging findings suggest that excessive Internet use shows functional and structural brain changes similar to substance addiction. Even though it is still under debate whether there are gender differences in case of problematic use, previous studies by-passed this question by focusing on males only or by using gender matched approach without controlling for potential gender effects. We designed our study to find out whether there are structural correlates in the brain reward system of problematic Similarl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 47 publications
4
22
0
Order By: Relevance
“…As in our previous study (Altbäcker et al, 2016) and those of others (Park et al, 2017;Yuan et al, 2013), we found differences between IAs and controls. The left STC was found to be thicker for controls.…”
Section: Group Differencessupporting
confidence: 88%
See 1 more Smart Citation
“…As in our previous study (Altbäcker et al, 2016) and those of others (Park et al, 2017;Yuan et al, 2013), we found differences between IAs and controls. The left STC was found to be thicker for controls.…”
Section: Group Differencessupporting
confidence: 88%
“…Moreover, addictive behavior could further increase impulsivity (de Wit, 2009). Furthermore, a large body of research (Altbäcker et al, 2016;Kühn & Gallinat, 2015;Park et al, 2017;Yuan et al, 2013) have shown that IA has an influence on the morphology of several brain regions. Thus, it seems plausible to claim that the effects of impulsivity, combined with long-term exposure to some specific substance or stimuli, might result in different natures of the relationships between impulsivity and brain structure when compared to HCs.…”
Section: The Distinctive Connection Between Trait Impulsivity and Cormentioning
confidence: 99%
“…The gray matter volume of ACC was negative correlated with the incongruent response errors of Stroop task in IGD group [24]. Decreased gray matter volume in similar brain regions were revealed by several other VBM studies of IGD [25][26][27]. Moreover, compared with health normal controls, the individuals with IGD showed increased cortical thickness in the left precentral cortex, precuneus, middle frontal cortex, inferior temporal and middle temporal cortices and decreased cortical thicknesses of the left lateral OFC, insula, lingual gyrus, the right postcentral gyrus, entorhinal cortex and inferior parietal cortex [28].…”
Section: Structural Findings By Mrisupporting
confidence: 59%
“…However, our sample did not include adolescents. When problematic internet behaviors in adolescents were assessed in Korean youth, those were more prevalent in males (Ha and Hwang, 2014), nevertheless, similar structural brain changes have been identified in females with PIU (Altbäcker et al., 2015). In a recent study, about half of the individual differences in compulsive online behaviors were accounted for by genetic factors to an equal degree in both genders.…”
Section: Discussionmentioning
confidence: 69%